STI diagnosis and HIV testing among OEF/OIF/OND Veterans - Goulet, Joseph L. (Med Care, 2014)
IMPORTANCE: Patients with an STI diagnosis should be tested for HIV, regardless of previous HIV test results. OBJECTIVE: Estimate HIV testing rates among recent service Veterans with an STI diagnosis and variation in testing rates by patient characteristics. DESIGN, SETTING, AND PARTICIPANTS: The sample comprised 243,843 Veterans who initiated Veterans Health Administration (VHA) services within one year after military separation. Participants were followed for two years to determine STI diagnoses and HIV testing rates. We used relative risks regression to examine variation in testing rates. MAIN OUTCOMES AND MEASURES: We used VHA administrative data to identify STI diagnoses and HIV testing and results. RESULTS: Veterans with an STI diagnosis (n=1,815) had higher HIV testing rates than those without (34.9% vs. 7.3%, p<0.0001), but were not more likely to have a positive test result (1.1% vs. 1.4%, p=0.53). Among Veterans with an STI diagnosis, testing increased from 25% to 45% over the observation period; older age was associated with a lower rate of testing, while race and ethnicity, multiple deployments, PTSD, and substance abuse disorders were associated with a higher rate. CONCLUSIONS AND RELEVANCE: Since VHA implemented routine HIV testing, overall rates of testing have increased. However, among Veterans at significant risk for HIV because of an STI diagnosis, only 45% had an HIV test in the most recent year of observation. Other patient characteristics such as alcohol and drug abuse were associated with being tested for HIV. Providers should be reminded that an STI is a sufficient reason to test for HIV.